The Implications of ‘Oumuamua on Panspermia - David Cao; Peter Plavchan; Michael Summers (The Astrophysical Journal, 2024)
Panspermia is the hypothesis that life originated on Earth from the bombardment of foreign interstellar ejecta harboring polyextremophile microorganisms. Since the 2017 discovery of the interstellar body ‘Oumuamua (1I/2017 U1) by the Pan-STARRS telescope, various studies have reexamined panspermia based on updated number density models that accommodate for ‘Oumuamua’s properties. By utilizing ‘Oumuamua’s properties as an anchor, we estimate the mass and number density of ejecta in the interstellar medium ( ρ _m [units of kg au ^−3 ] and ρ _n [units of au ^−3 ]). We build upon prior work by first accounting for the minimum ejecta size to shield microbes from supernova radiation. Second, we estimate the total number of impact events C _n on Earth after its formation and prior to the emergence of life (≈0.8 Gyr). We derive a conditional probability relation for the likelihood of panspermia for Earth specifically of <10 ^−5 , given a number of factors including f _B , the fraction of ejecta harboring extremophiles and other factors that are poorly constrained. However, we find that panspermia is a plausible potential life-seeding mechanism for (optimistically) potentially up to ∼10 ^5 of the ∼10 ^9 Earth-sized habitable zone worlds in our Galaxy.